Anakinra for recalcitrant pyoderma gangrenosum. (1st December 2021) - O'Connor, C.; Gallagher, C.; Hollywood, A.; Paul, L.; O'Connell, M.
Summary: Pyoderma gangrenosum (PG) is an autoinflammatory neutrophilic dermatosis characterized by rapidly enlarging, painful ulcers. Anakinra is a recombinant interleukin (IL)‐1 receptor antagonist that blocks the activity of IL‐1α and IL‐1β by competitively inhibiting IL‐1 binding to the IL‐1 type 1 receptor. We present a series of two patients with recalcitrant PG, who had limited therapeutic options and multiple comorbidities and multiple previous treatment failures, who obtained 100% healing with anakinra. Compared with conventional first‐line therapies for PG, the safety profile of anakinra may be preferable for patients with multiple comorbidities. Further research is needed to assess the safety and efficacy of anakinra for PG.